Interagency programmatic approach to organize public health promotion events in Moscow - L. А. Mylnikova; N. N. Kamynina (Здоровье мегаполиса)
The purpose of the research is to provide a comprehensive analysis of approaches to the organization of events for the implementation of Moscow’s development programs, from the point of view of strengtheningpublic health. Materials and methods. The methods of the study are: the integrated assessment of data of industry statistical reporting, the method of descriptive statistics, the method of content analysis. Approaches to the organization of events of the state programs of the city of Moscow, from the point of view of strengthening public health, are defined. It is shown that the state programs include areas related to strengthening public health, their implementation is carried out jointly by various departments and is of an interdepartmental nature. Urban planning policy and development of the territories of the city of Moscow is carried out in accordance with the analysis of the environmental situation, demography, and social needs of citizens. Correlation between the state of public health in Moscow according to the results of clinical examination and ongoing activities of state programs of Moscow, shows the relevance of interagency measures to enhance public health and promote a healthy lifestyle. Results. The results of medical examinations in 2017−2019 show that it is necessary to strengthen interdepartmental measures aimed at strengthening public health in the city of Moscow.